1989
DOI: 10.1088/0029-5515/29/3/007
|View full text |Cite
|
Sign up to set email alerts
|

Impurity transport in ohmically heated TFTR plasmas

Abstract: The paper presents a study of impurity transport in ohmically heated TFTR plasmas by computer modelling of VUV line emissions from impurities injected using the laser blow-off technique. The results are sensitive to uncertainties in the ionization and recombination rates used in the modelling and, therefore, only a spatially averaged diffusion coefficient and parameterized convective velocity can be measured. Measurements of these transport parameters are presented for deuterium and helium discharges with Ip =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Unfortunately, detailed comparisons with these previous works are not possible. For instance, the line brightnesses of Ge ions injected by laser blowoff in the TFTR tokamak plasmas have been simulated [8] using the MIST code [9]. Details of the rates used and of the ionization balances were not published, which makes comparison impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, detailed comparisons with these previous works are not possible. For instance, the line brightnesses of Ge ions injected by laser blowoff in the TFTR tokamak plasmas have been simulated [8] using the MIST code [9]. Details of the rates used and of the ionization balances were not published, which makes comparison impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not entirely clear how m is defined. Indeed, it could be assumed that collisional and/or turbulent transport in the plasma can contribute to m along with atomic processes, e.g., as a simple sum as observed in experiments with light impurities (see, e.g., in [12,42]). for two types of equilibrium that differ in the total density profile (see Figure 7a).…”
Section: The Radial Scale Of the Cs Equilibriummentioning
confidence: 99%
“…In the extensive practice of modeling medium and heavy impurities and with an increase in the rates of ionization-recombination it was found that the DCM sensitivity to the empirical transport remains extremely low [7][8][9][10][11][12][13] and just unacceptable for W impurity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the practice of modeling medium and heavy impurities, that is, with an increase in the rates of ionization-recombination, it was found that the DCM sensitivity to the empirical transport coefficients remains extremely low [7][8][9][10][11][12][13] and just unacceptable for W impurity [14,15].…”
Section: Introductionmentioning
confidence: 99%